The Beneficience Of Family Social Support Toward Anticipatory Behaviour Of Pregnancies Sign’s Alert In Primigravida - Aditiawarman Aditiawarman; Ni Ketut Alit Armini; Yunita Ike Kristanti (Jurnal Ners, 2008)
Introduction: Complication in pregnancy can be endangering both mother and fetus. Pregnant woman and her family must be able to recognize risk factors of the complication. Family support make pregnant woman feel more confident, happy and ready to face her pregnancy. The aimed of this study was to learn the influences of social family support toward anticipatory behavior of pregnancies sign’s alert in primigravida.Methods: A quasy experimental purposive sampling design was used in this study. There were 20 respondents who met the inclusion criteria. They were divided into 2 groups, intervention and control groups, each comprising 10 respondents. The independent variable in this study was social family support and the dependent variable was the anticipatory behavior of pregnancies sign’s alert in primigravida. Data were collected by using questionnaire, observation and structured interview and then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level α≤0.05.Results: The result showed that the social family support influencing the knowledge of pregnant woman with significant level p=0.011, social family support also influencing the attitude of pregnant woman with significant level p=0.008 and the action of pregnant woman p=0.017. There were difference knowledge, attitude and action between intervention and control groups after treatment with significant level p=0.000 for knowledge, p=0.015 for attitude and p=0.002 for action.Conclusion: It can be concluded that social family support influence anticipatory behavior (knowledge, attitude and action) of pregnancies sign’s alert in primigravida. Further studies should be concern to the other factors that influencing the anticipatory behavior of pregnancies sign’s alert in primigravida, both of internal and external factors.